Doping in conjugated polymers - Kar, Pradip (Polymer science and plastics engineering., 2013)
This book responds to the growing interest in conjugated polymer-dopant interaction across disciplines. The first book dedicated to the subject, it offers an A to Z overview, detailing doping interaction, dopant types, doping techniques, influence of dopant on applications, and more. It explains how the performances of these polymers are influenced by the nature of dopants and their level of distribution within the polymer, showing how the electrochemical, mechanical, and optical properties of the doped conjugated polymers can be tailored by various means.